ANALISIS STRATEGI PEMBIAYAAN DALAM UPAYA OPTIMALISASI KONSEP GREEN FINANCE (Studi Kasus Pada Bank Rakyat Indonesia Syariah Kantor Cabang Malang) - ISTIOWATI, SRI INDAH (Jurnal Ilmu Manajemen Advantage, 2018)
The concept of Green Finance (Triple Bottom Line), Profit, People and Planet which emphasized for optimization economic factors, attention to the sustainability of environmental factors. The community demanded that company follow concept of Green Finance to achieve environmental improvement balanced with economic development. Banks should apply concept of Green Finance to maintain environmental conditions. The purpose research is to know the application of Green Finance at Bank Rakyat Indonesia Syariah Branch Malang and optimize the existing Green Finance by using SWOT Analysis. This research use descriptive qualitative approach. Object of this study was taken at PT Rakyat Indonesia Syariah Branch Malang, uses research method, data reduction, data display, conclusion and verification. The results showed that implementation of Green Finance at Bank Rakyat Indonesia Syariah Branch Malang not only to improve the economic level of the customer, but also social awareness and environmental analysis with AMDAL. Bank Rakyat Indonesia Syariah Branch Malang have potential to became bank which to maintain economic and natural stability, and strive the needs of funds desired by customers. Bank Rakyat Indonesia Syariah Branch Malang optimize balancing aspects of people, the planet (environment), and profit (economy), in financing, Account Officers keep in providing financing comfort to customer